Advanced strategies for detecting acid sphingomyelinase deficiency type B with attenuated phenotypes - Thomas Villeneuve; Thibaut Jamme; Robin Schwob; Thierry Levade; Grégoire Prévot (Orphanet Journal of Rare Diseases)
Abstract Background Acid Sphingomyelinase Deficiency (ASMD) type B is a rare lysosomal disorder caused by SMPD1 mutations. Due to its low prevalence and clinical heterogeneity, diagnosis is challenging, and detection is crucial for the initiation of enzyme replacement therapy. Methods We conducted a retrospective study (RnIPH 2024-85) at Toulouse University Hospital, analyzing 359,802 lipid profiles (2012–2023). We identified individuals with a total cholesterol/HDL cholesterol ratio > 4.5. A regex-based extraction method screened records for consanguinity, hepatomegaly, splenomegaly, and ground-glass opacities (GGOs), while we also analyzed thrombocytopenia (< 150 × 10⁹/L). Patients meeting ≥ 4/5 criteria underwent clinical review. Results Among 63,653 patients with dyslipidemia, 20.3% had thrombocytopenia, 4.93% hepatosplenomegaly, 2.29% GGOs, and 0.24% consanguinity. In total, 179 patients met ≥ 4/5 criteria. Nineteen (10.6%) were pediatric. Three previously diagnosed ASMD type B patients in our center were identified. Additionally, among other conditions, 46 cases (25.7%) had monogenic diseases, and five undiagnosed patients were flagged for ASMD screening. Conclusion Our hybrid screening effectively identified ASMD type B cases and potential candidates for genetic testing. This approach combining algorithmic filtering and clinical expertise, could enhance ASMD type B diagnosis.